Use of social networks by pre-graduate students in a school of medicine in Lima, Peru - Guillén López, Otto Barnaby (2019)
The use of the internet has increased significantly over the last decade. Pre-graduate students use the internet and social networks not only for recreational activities but also for academic activities. Moreover, some schools of medicine use these resources to teach medical students. Objective: To describe the use of social networks by pre-graduate medical students. Methods: A cross-sectional study was carried-out by using a questionnaire among pre-graduate medical students of the fifth year. Wes asked about which social network the student has an active account, time spent using the network and how frequent the network was visited focusing on Facebook® y YouTube®. Results: 52 students participated; all of them had an account in Facebook®, 46.2% in Instagram®, 34.6% in Twitter®, 15.4% in SlideShare® y 7.7% in LinkedIn®. Among those who had an account in Facebook®, 50% use it at least one-hour per day; 65.3% watched videos in YouTube®. Conclusions: All students used at least one social network, mostly Facebook®, and use it at least once per day, this finding is similar to what has been reported elsewhere.